2019
DOI: 10.1371/journal.pone.0210334
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the extended thrombolysis in cerebral infarction score in a real world cohort

Abstract: BackgroundA thrombolysis in cerebral infarction (TICI) score of 2b is defined as a good recanalization result although the reperfusion may only cover 50% of the affected territory. An additional mTICI2c category was introduced to further differentiate between mTICI scores. Despite the new mTICI2c category, mTICI2b still covers a range of 50–90% reperfusion which might be too imprecise to predict neurological improvement after therapy.AimTo compare the 7-point “expanded TICI” (eTICI) scale with the traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Multiple randomized trials have demonstrated the benefit of mechanical thrombectomy (MT) for acute ischemic stroke due to large vessel occlusion (LVO) [1,2]. Clinical outcome after MT can be improved by an increasing degree of reperfusion evaluated by the expanded thrombolysis in cerebral infarction (eTICI) scale [3,4]. Accordingly, complete reperfusion (TICI 3) is leading to a markedly better outcome with the highest rate of excellent functional outcome (mRS ≤ 1) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple randomized trials have demonstrated the benefit of mechanical thrombectomy (MT) for acute ischemic stroke due to large vessel occlusion (LVO) [1,2]. Clinical outcome after MT can be improved by an increasing degree of reperfusion evaluated by the expanded thrombolysis in cerebral infarction (eTICI) scale [3,4]. Accordingly, complete reperfusion (TICI 3) is leading to a markedly better outcome with the highest rate of excellent functional outcome (mRS ≤ 1) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, the use of intra-arterial thrombectomythe mechanical removal of a clot via a stenthas become the standard of care for patients with acute ischaemic stroke caused by large vessel occlusion [4,5]. Despite this, many patients do not recover full perfusion in their tissue downstream of the recanalized vessel [6]. This observation, commonly known as the "no-reflow" or "no-reperfusion" phenomenon, has been documented in numerous studies involving both animals and humans [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Safety endpoints will include symtomatic ICH at 24 hours specified according to the Heidelberg Bleeding Classification 11 -defined as a new ICH as detected by brain imaging after 24 hours of intervention associated with: ► ≥4 points worsening of total NIHSS score at the time of diagnosis compared with immediately before deterioration ► ≥2 point worsening in one NIHSS category ► Leading to intubation/hemicraniectomy/external ventricular drain placement or other major medical/surgical intervention ► Absence of alternative explanation for deterioration.…”
Section: Clinical Efficacymentioning
confidence: 99%